Implementasi Kurikulum Merdeka dalam Mata Pelajaran PAI di SD Negeri 15 Koto Lalang - Mardawila Adha Anjeli; Afif Putra Nazwan; Novita Juliana Sari Indah; Sasminelwati; Misra (Risâlah Jurnal Pendidikan dan Studi Islam, 2024)
In Indonesia, the implementation of the curriculum has undergone various changes and improvements, namely the thirteen curriculum, after which in 2018 it became the thirteen revised curriculum and when Indonesia due to the impact of the co-19 pandemic turned into an emergency curriculum and then refined again into an independent learning curriculum. This study discusses how the implementation of the independent curriculum, especially PAI subjects. The research method uses qualitative research, the descriptive method aims to describe, describe, and analyze objects systematically on the implementation of the independent learning curriculum in schools, especially in Islamic Religion subjects. Data collection techniques based on observation, interviews and documentation. Data processing techniques are carried out by making interview instruments. The technique of analyzing data is data reduction, data presentation and conclusion drawing. The research location is SD Negeri 15 Koto Lalang. Conducted on December 7, 2023. The research subject was the PAI teacher of SD Negeri 15 Koto Lalang. Results and discussion First, the teacher's understanding of the independent learning curriculum and has been implemented well. It's just that there are still aspects that require teachers to be more creative and innovative in carrying out the learning process based on the independent curriculum. Second, the benefits felt after implementing the independent curriculum are that the independent curriculum focuses more on freedom and creative thinking.